2020
DOI: 10.1002/bit.27305
|View full text |Cite
|
Sign up to set email alerts
|

Promoting bidirectional extracellular electron transfer of Shewanella oneidensis MR‐1 for hexavalent chromium reduction via elevating intracellular cAMP level

Abstract: The bioreduction capacity of Cr(VI) by Shewanella is mainly governed by its bidirectional extracellular electron transfer (EET). However, the low bidirectional EET efficiency restricts its wider applications in remediation of the environments contaminated by Cr(VI). Cyclic adenosine 3′,5′‐monophosphate (cAMP) commonly exists in Shewanella strains and cAMP–cyclic adenosine 3′,5′‐monophosphate receptor protein (CRP) system regulates multiple bidirectional EET‐related pathways. This inspires us to strengthen the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…Adenylate cyclase expressing S. oneidensis MR−1 exhibited enhanced bidirectional EET and Cr(VI) reduction capacities. This was attributed to increased production of cyclic adenosine 3 ,5 −monophosphate (cAMP) and cAMP-receptor protein system, which enhanced the gene expression of c−type cytochromes and flavins synthetic pathways for Cr(VI) reduction (Cheng et al, 2020). Similarly, the outer membranes of Geobacter spp.…”
Section: Other Chemical Influencesmentioning
confidence: 99%
“…Adenylate cyclase expressing S. oneidensis MR−1 exhibited enhanced bidirectional EET and Cr(VI) reduction capacities. This was attributed to increased production of cyclic adenosine 3 ,5 −monophosphate (cAMP) and cAMP-receptor protein system, which enhanced the gene expression of c−type cytochromes and flavins synthetic pathways for Cr(VI) reduction (Cheng et al, 2020). Similarly, the outer membranes of Geobacter spp.…”
Section: Other Chemical Influencesmentioning
confidence: 99%
“…Briefly, several LuxR homologous genes are predicted in the genomes of Shewanella spp. including S. woodyi MS32 and S. baltica (Li J. et al, 2020;Hayek et al, 2020). The genome of S. oneidensis is predicted to contain seven putative LuxR family proteins.…”
Section: Quorum Sensing Systems In the Development Of Geobacter And Shewanella Biofilmsmentioning
confidence: 99%
“…The presence of both IPTG and AHL activates MtrA expression, which restores the EET pathway and increases electricity output (Hu et al, 2015). In another study, the lux QS system was used to construct a population-state decision system for intelligently reprogramming the EET regulation system (Li F.-H. et al, 2020). The EET-related genes or pathways, such as cymA, shuttle exporter genes or flavin biosynthesis pathway, were located at the downstream of QS system and could be expressed at a certain population-state threshold.…”
Section: Chemical Signaling-targeted Biofilm Engineering For Electricity Generation In Mfcsmentioning
confidence: 99%
“…In particular, by replacing with CctA a few terminal reductases, including NrfA, FccA, and NapA (periplasmic nitrate reductase), Delgado et al (2019) observed significantly increased ferric iron reduction rate and current generation. In addition, enhanced production of a large portion of c-Cyts by elevated cAMP levels, the effector molecule for Crp which is the primary transcriptional activator for anaerobic respiration, has also been found to be effective (Kasai et al, 2019;Cheng et al, 2020).…”
Section: Introductionmentioning
confidence: 99%